Clinical assessment of oral mucositis and candidiasis compare to chemotherapic nadir in transplanted patients - PATUSSI Cleverson; SASSI Laurindo Moacir; MUNHOZ Eduardo Ciliao; ZANICOTTI Roberta Targa Stramandinoli; SCHUSSEL Juliana Lucena (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Oral mucositis is a chief complication in patients undergoing hematopoietic stem cell transplantation (HSCT). It is considered a toxic inflammatory reaction that interferes with the patient's recuperation and quality of life. Oral candidiasis is a common fungal infection observed in dental practice, particularly in immunocompromised patients. The aim of this study was to evaluate the presence of oral mucositis and oral candidiasis in patients who underwent HSCT and their correlation with the chemotherapeutic nadir (lowest possible outcome). We evaluated patients with different diagnoses who underwent HSCT at the Hospital Erasto Gaertner. No chemotherapeutic nadir curves could be associated with mucositis, and patients had different presentations of mucositis. No patient developed oral candidiasis during hospitalization. Together with cell counts, we collected demographic data including age, oral hygiene, habits harmful to health, and the use of oral prostheses. It was observed that patients who smoked cigarettes before hospitalization showed less mucositis, resulting in no feeding problems or other comorbid conditions due to the effect of mucositis. However, the nadir of the chemotherapy curve, in isolation, is not a predictive tool for the appearance (or no appearance) of oral mucositis.